HESITANGES ABOUT COVID-19 VACCINATION AMONG STUDENTS, TEACHERS AND PARENTS - Miglena Tarnovsk; Gergana Petrova; Emilya Avramova-Bakalova (Peytchinski Publishing, 2024)
Vaccination is a leading strategy for the prevention and control of individual and public health in the fight against the COVID-19 pandemic. Purpose: This study aims to investigate and analyze the attitudes toward vaccination and the factors conditioning hesitancy about the vaccine´s prevention of COVID-19 among three target groups: students, parents and teachers. Materials and methods: An online anonymous survey was conducted among 228 participants - students in 11th and 12th grade at two language high schools in the city of Plovdiv (n=114), teachers (n=44) and parents (n=70) in November 2021 Results: Vaccination attitudes were fairly heterogenous, ranging from complete agreement to categorical disagreement in the answers of all three studied groups. The prevailing opinion among parents is that vaccination has no absolute protective effect regarding the risk of infection with COVID-19. Both parents and teachers, as well as students, strongly object to mandatory vaccination against COVID-19. An important factor influencing the hesitancy of vaccine prevention is the concern of whether the new vaccines are harmless and effective. Negative expectations of possible adverse reactions to the administered vaccines are shared among half of the students and a significant part of the studied group of parents and teachers. Conclusions: Established factors influencing vaccine hesitancy should be considered when conducting future vaccination trial campaigns for immunoprophylaxis among adolescents.